The contribution of color information to rapid face categorization in natural scenes - Or, Charles C.-F. (2019)
Color’s contribution to rapid categorization of natural images is debated. We examine its effect on high-level face categorization responses using fast periodic visual stimulation (Rossion et al., 2015). A high-density electroencephalogram (EEG) was recorded during presentation of sequences of natural object images every 83 ms (i.e., at F ¼ 12.0 Hz). Natural face images were embedded in the sequence at a fixed interval of F/ 9 (1.33 Hz). There were four conditions: (a) full-color images; (b) grayscale images; and (c) and (d) phasescrambled images from Conditions 1 and 2, respectively, making faces and objects unrecognizable. Observers’ task was to respond to color changes of the fixation cross (Experiment 1). We found face-categorization responses at 1.33 Hz and its harmonics (2.67 Hz, etc.) over occipitotemporal areas, with right-hemisphere dominance; responses to color images were not significantly different from those to grayscale images. Behavioral analysis revealed longer response times when images contained color, despite nearly-all-correct performance in all conditions, suggesting that color change in the task might detract from color’s contribution to face categorization. We subsequently changed the task to responding to fixation shape changes so that such response-time differences were eliminated (Experiment 2). The aggregate facecategorization response became 21.6% stronger to color than to grayscale images. This color advantage occurred late, at 290–415 ms after stimulus onset. Our results suggest that the color advantage for face categorization interacts with behavior, and that color only has a moderate and relatively late contribution to rapid face categorization in natural images.